2006
DOI: 10.1007/s10531-006-9084-z
|View full text |Cite
|
Sign up to set email alerts
|

Testing indicators of epiphytic lichen diversity: a case study in N Italy

Abstract: The predictability of a standardized and widely used biomonitoring method for estimating total lichen diversity on trunks (LDV-index) was tested. The study was carried out in Veneto (NE Italy), on 34 randomly selected trees in five sites in different landscape contexts. Two sets of biodiversity data were obtained from each tree: (1) the LDV index based on species frequency within a standard sampling grid positioned on a limited part of the trunks only (2) the total number of species found on the trunks. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The selection of indicators, however, may be problematic (e.g. Kerr et al 2000;Landers et al 1988;Noss 1990), and their correlation with the overall diversity must be tested (Hedenås and Ericson 2000;Bergamini et al 2005;Nascimbene et al 2006;Nordén et al 2007). For a rapid assessment of tree-level species richness both structural and biological indicators could be used.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of indicators, however, may be problematic (e.g. Kerr et al 2000;Landers et al 1988;Noss 1990), and their correlation with the overall diversity must be tested (Hedenås and Ericson 2000;Bergamini et al 2005;Nascimbene et al 2006;Nordén et al 2007). For a rapid assessment of tree-level species richness both structural and biological indicators could be used.…”
Section: Discussionmentioning
confidence: 99%
“…This is because various lichen communities are susceptible to local species loss due to disturbance (Pharo et al 2000;Uliczka and Angelstam 2000;Nordén and Appelqvist 2001). Additionally, lichen communities can also become dominated by species that are resistant to the effects of disruption or pollution (Jüriado et al 2003;Humphrey et al 2002;Will-Wolf et al 2002;Brunialti and Giordani 2003;Nascimbene et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For the quantification of visible damage, we decided to use macrolichens as bioindicators since Nascimbene et al [76] demonstrated that a sample of macrolichens, or even only large-lobed foliose lichens, allows the diversity to be reliably estimated. Moreover, in this type of lichen, it is easier to visualise a gradient of damage and, therefore, to obtain a more robust assessment.…”
Section: Lichen Damage Index (Di)mentioning
confidence: 99%